1991
DOI: 10.1093/oxfordjournals.jhered.a111088
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse Mutation Claw Paw: Forelimb Deformity and Delayed Myelination throughout the Peripheral Nervous System

Abstract: We describe a murine autosomal recessive mutation claw paw (gene symbol clp), which in homozygous clp/clp mice produces striking abnormalities of limb posture within the first one or two postnatal days. Affected animals have delayed and abnormal myelination in the peripheral nervous system but not in the central nervous system, and also have persistently blocked myelination of small caliber axons that are myelinated in normal mice. Both abnormalities suggest that an important effect of the clp mutation is to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…This phenotype was sometimes observed as early as birth, and was readily observable by P4. This limb phenotype is reminiscent of human patients with arthrogryposis multiplex congenita (AMC) (Bamshad et al, 2009) and has also been reported in mouse Adam22 mutants (Nishino et al, 2010) and mouse claw paw mutants (Henry et al, 1991;Darbas et al, 2004), which have a mutation in the Lgi4 gene (Bermingham et al, 2006). In addition to these limb posture abnormalities, sciatic nerves in Gpr126-/-mice were severely reduced in size with a hypomyelinated (i.e.…”
Section: Nerve and Limb Defects In Gpr126-/-micementioning
confidence: 58%
See 2 more Smart Citations
“…This phenotype was sometimes observed as early as birth, and was readily observable by P4. This limb phenotype is reminiscent of human patients with arthrogryposis multiplex congenita (AMC) (Bamshad et al, 2009) and has also been reported in mouse Adam22 mutants (Nishino et al, 2010) and mouse claw paw mutants (Henry et al, 1991;Darbas et al, 2004), which have a mutation in the Lgi4 gene (Bermingham et al, 2006). In addition to these limb posture abnormalities, sciatic nerves in Gpr126-/-mice were severely reduced in size with a hypomyelinated (i.e.…”
Section: Nerve and Limb Defects In Gpr126-/-micementioning
confidence: 58%
“…Gpr126-/-nerve pathology is also reminiscent of defects observed in Adam22 and Lgi4 mutants (Henry et al, 1991;Darbas et al, 2004;Sagane et al, 2005;Ozkaynak et al, 2010;Nishino et al, 2010). Adam22 is a receptor for Lgi4; Adam22 is expressed neuronally, and Lgi4 is secreted principally by Schwann cells in peripheral nerve (Sagane et al, 2008;Ozkaynak et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth member of this protein family, LGI4, has been associated with childhood convulsions and absence epilepsy (Gu et al, 2004;Ishii et al, 2010). Moreover, targeted and spontaneous (claw paw mice; Lgi4 clp ) mutations in Lgi4 in mice cause severe congenital hypomyelination of the developing peripheral nervous system (PNS) and premature death (Bermingham et al, 2006;Henry et al, 1991;Nishino et al, 2010;Ozkaynak et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between LGI4 and ADAM22 is required for timely axonal sorting and myelination (Bermingham et al, 2006;Henry et al, 1991;Sagane et al, 2005), developmental processes that involve extensive interactions between the axonal and Schwann cell membranes. ADAM23 is expressed in the PNS and in particular in Schwann cells (Dhaunchak et al, 2010), but its role in axonal sorting and myelination has not been explored.…”
Section: Introductionmentioning
confidence: 99%